2007
DOI: 10.1002/jssc.200700064
|View full text |Cite
|
Sign up to set email alerts
|

Fast and simple online sample preparation coupled with capillary LC‐MS/MS for determination of prostaglandins in cell culture supernatants

Abstract: An online 2-D strong cation exchange (SCX)-RP capillary liquid chromatographic (cLC) method with IT mass spectrometric (IT-MS/MS) detection for the simultaneous determination of prostaglandin (PG) A(1), PGD(2), PGE(1), PGE(2), PGF(2a), 6-keto-(6k)PGF(1a), and 15-Delta(12,14)-deoxy-PGJ(2) (15dPGJ(2)) in cell culture supernatants was developed and validated. Pretreatment of the cell culture supernatants included dilution and filtration, and the analysis time including all sample preparation steps was less than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Prostanoids are released by stem cells upon stimulation; however their concentration is highly variable [3]. With our previously developed method concentrations in the range of 0.4 -2.2 ng/mL cell culture supernatant could be determined [3].…”
Section: Methods Optimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Prostanoids are released by stem cells upon stimulation; however their concentration is highly variable [3]. With our previously developed method concentrations in the range of 0.4 -2.2 ng/mL cell culture supernatant could be determined [3].…”
Section: Methods Optimizationmentioning
confidence: 99%
“…Previously, we reported that nonstimulated hMSCs release PGE 2 , and stimulated hMSCs release PGE 1 and PGE 2 (unpublished manuscript, [3]). However, we also found evidence for other PGs to be present at lower concentrations.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations